Presenting JAK inhibitor safety information to dermatology patients - Anthony J. Teixeira; Jessica Q. Duong; Shirley P. Parraga; Steven R. Feldman (JEADV Clinical Practice)
Abstract Janus Kinase (JAK) inhibitors are treatment options for dermatologic conditions such as atopic dermatitis, psoriasis, vitiligo, and alopecia areata. Guidance on how to counsel patients on these novel treatments is limited. The purpose of this review is to provide options providers can use to discuss JAK inhibitors with dermatology patients. The PubMed database was searched for terms including “dermatology JAK inhibitor safety” and “presenting information to patients.” Relevant literature was selected for inclusion. Black box warnings were placed on JAK inhibitors after a large, controlled trial in rheumatoid arthritis patients did not prove that tofacitinib was as safe as tumor necrosis factor inhibitors; in clinical trials for dermatologic conditions, JAK inhibitors had low risks of serious adverse events. Patient barriers to comprehending treatment information include conflicting information and limited time for discussion of risks. To address these barriers, suggested approaches have included speaking in simple phrases, providing reliable sources, and offering educational materials appropriate for different cultures. When discussing risks, physicians may use anecdotes and frame risks and side effects in ways that decrease anxiety. JAK inhibitors have uncommon severe side effects and related concerns that may be hard for patients to overcome, even when benefits exceed risks. Standard educational approaches can be complemented by anecdotes and framing to help diminish patients' anxiety.